Risk of metachronous colorectal cancer following colectomy in Lynch syndrome: a systematic review and meta‐analysis. (June 2017) - Anele, C. C.; Adegbola, S. O.; Askari, A.; Rajendran, A.; Clark, S. K.; Latchford, A.; Faiz, O. D.
Abstract: Aim: Lynch syndrome (LS) accounts for 2–4% of all colorectal cancer (CRC) cases, and is associated with an increased risk of developing metachronous colorectal cancer (mCRC). The role of extended colectomy in LS CRC is controversial. There are limited studies comparing the risk of mCRC following segmental colectomy and extended colectomy. The objective of this systematic review is to evaluate the risk of developing mCRC following segmental and extended colectomy for LS CRC and endoscopic compliance. Method: A systematic review of major databases was performed using predefined terms. All original articles published in English comparing the risk of mCRC in LS patients after segmental and extended colectomy from 1950 to January 2016 were included. Results: The search retrieved 324 studies. Six studies involving 871 patients met the inclusion criteria. Of these, 705 (80.9%) underwent segmental colectomy and 166 (19.1%) extended colectomy. Average follow‐up was 91.2 months. The mCRC rate was 22.8% and 6% in the segmental and extended colectomy groups, respectively. The segmental group were over four times more likely to develop mCRC (OR 4.02, 95% CI: 2.01–8.04, P  < 0.0001). mCRC occurred in patients after segmental colectomy despite 1–2‐yearly postoperative endoscopic surveillance. Conclusion: This result suggests that extended colectomy reduces the risk of mCRC by over four‐fold compared with segmental colectomy. mCRC occurred in the segmental group despite postoperative endoscopic surveillance. This needs to be borne in mind when deciding on the appropriate surgical management of LS patients with CRC. We recommend that extended colectomy should be considered for patients with confirmed LS CRC.